2021
DOI: 10.24123/aipj.v36i2.3053
|View full text |Cite
|
Sign up to set email alerts
|

The Work Stress of Millennial Employees Reviewed from the Viewpoint of Organizational Climate with Team-Member Exchange as a Moderator [Stres Kerja Karyawan Milenial Ditinjau dari Iklim Organisasi dengan Team-Member Exchange sebagai Moderator]

Abstract: This study aims to define the role of organizational climate on work stress of millennial employees and the moderating effect of team-member exchange in the relationship between organizational climate and work stress of millennial employees. Participants are employees born in the time range of 1980 to 2000 and have worked for at least six months. This study utilized survey method with the instruments Stress Diagnostic Survey, Organization Climate Questionnaire, and Team-Member Exchange (TME) instrument which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…This specific age group was the most under pressure due to the rise of perfectionism and efficiency demands in their generation [8], which can affect their susceptibility to occupational stress. In a survey conducted, it showed that the highest levels of work stress were experienced by this generation [9]. Therefore, as age contributes to certain factors that affect susceptibility to occupational stress, it was a major determinant in occurrence of occupational stress in specific age groups -certain age groups were more likely to experience occupational stress than others.…”
Section: Relationship Between the Demographic Profile Of The Responde...mentioning
confidence: 99%
“…This specific age group was the most under pressure due to the rise of perfectionism and efficiency demands in their generation [8], which can affect their susceptibility to occupational stress. In a survey conducted, it showed that the highest levels of work stress were experienced by this generation [9]. Therefore, as age contributes to certain factors that affect susceptibility to occupational stress, it was a major determinant in occurrence of occupational stress in specific age groups -certain age groups were more likely to experience occupational stress than others.…”
Section: Relationship Between the Demographic Profile Of The Responde...mentioning
confidence: 99%
“…Karakteristik ini membuat generasi milineal rentan terhadap tekanan dan mudah mengalami stres hingga burnout di tempat kerja (Juniman, 2018;Thaariq, 2022). Pada titik ini dapat dipahami bahwa sebaiknya karyawan milenial dapat mengembangkan resiliensi di tempat kerja.…”
unclassified